(untitled) - Harvey, David (Boston, 2000)
Modern Analytical Chemistry is a one-semester introductory text that meets the needs of all instructors. With coverage in both traditional topics and modern-day topics, instructors will have the flexibilty to customize their course into what they feel is necessary for their students to comprehend the concepts of analytical chemistry
Các phương pháp phân tích hóa học hiện đại,Các kỹ thuật phân tích bề mặt
Keywords: Chemistry, Analytic